2003
DOI: 10.1016/s0011-393x(03)00129-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the radiographic contrast material iopamidol on hemostasis: an observational study in thirty cardiac patients

Abstract: Background: In vitro studies have shown that nonionic radiographic contrast material may induce the generation of thrombin in blood, whereas ionic contrast agents, such as iohexol, do not. However, knowledge of the effects of contrast material on coagulation and fibrinolytic systems in vivo is limited.Objective: This study was designed to assess the effects of the nonionic radiographic contrast material iopamidol on hemostasis in patients undergoing coronary angiography or cardiac catheterization.Methods: Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The slight increase in PT values in the control group can also be explained by the effect of contrast agents on PT. In a previous study, a signi cant increase in PT values was found with nonionic low osmolar iopamidol [26,27].…”
Section: Discussionmentioning
confidence: 76%
“…The slight increase in PT values in the control group can also be explained by the effect of contrast agents on PT. In a previous study, a signi cant increase in PT values was found with nonionic low osmolar iopamidol [26,27].…”
Section: Discussionmentioning
confidence: 76%
“…The slight increase in PT values in the control group can also be explained by the effect of contrast agents on PT. In a previous study, a significant increase in PT values was found with nonionic low osmolar iopamidol (27,28).…”
Section: Discussionmentioning
confidence: 77%
“…Conversely, toxic doses exclude the effect (35,36). Reduction in platelets at a minimum dose in males is difficult to explain by the damaging effect, as for example with iodine-containing preparations such as amiodarone or iopamidol (37,38). Moreover, this effect disappears at the maximum doses of PA.…”
Section: Discussionmentioning
confidence: 99%